Poster: Technology “The Flipped Classroom” in the Study of Mathematics at the Technical Universityy; Advances in Intelligent Systems and Computing; Vol. 1329 : Educating Engineers for Future Industrial Revolutions - Ustinova I. G. Irina Georgievna (2021, 2021)
Title screen